Evaluation of the nutritional quality of Chaetoceros muelleri Schütt (Chaetocerotales: Chaetocerotaceae) and Isochrysis sp. (Isochrysidales: isochrysidaceae) grown outdoors for the larval development of Litopenaeus vannamei (Boone, 1931) (Decapoda: Penaeidae) - Rodríguez Erika O.; López-Elías José A.; Aguirre-Hinojosa Eduardo; del Garza-Aguirre María C.; Constantino-Franco Francisco; Miranda-Baeza Anselmo; Nieves-Soto Mario (Archives of Biological Sciences, 2012)
The biomass, proximal composition and fatty acid profile of Isochrysis sp., Chaetoceros muelleri and their mixture, grown under greenhouse conditions, were evaluated. The nutritional value of both species supplied as the monoalgal (Chaetoceros muelleri: Diet I, and Isochrysis sp. Diet II) and mixed diet (Diet III) for larval Litopenaeus vannamei was also assessed on the basis of the development and biochemical composition of the larvae. The highest protein levels were obtained in Diets I and II (40% and 35%, respectively). No significant differences in larval survival were found among the diets; however, larvae fed on Diet II had the lowest mean larval length.